1988
DOI: 10.1530/jrf.0.0820447
|View full text |Cite
|
Sign up to set email alerts
|

Ovine follicular fluid inhibits thymidine incorporation by 3T3 fibroblasts in vitro

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A similar protein of molecular mass 10 kDa is present in ovine follicular fluid which inhibits [3H]thymidine incorporation in fibroblasts (Carson et al, 1988). The stimulatory effects were found in the molecular mass range of > 30 kDa.…”
Section: Discussionmentioning
confidence: 92%
“…A similar protein of molecular mass 10 kDa is present in ovine follicular fluid which inhibits [3H]thymidine incorporation in fibroblasts (Carson et al, 1988). The stimulatory effects were found in the molecular mass range of > 30 kDa.…”
Section: Discussionmentioning
confidence: 92%
“…Cahill et al demonstrated that ovine follicular fluid inhibited the development of follicles >2 mm in diameter in the ovary and reduced the mitotic index of the granulosa cells of follicles <2 mm (Cahill et al, 1985). Later, substances with molecular weights of 18 000 and <10 000 kDa were identified in ovine follicular fluid that inhibited the mitotic activity of murine embryonic lung fibroblasts (Carson et al, 1988). Campbell et al reported a substance in the ovine pre-ovulatory follicle that is atresia-inducing and results in a loss of steroidogenic activity following injection into the cycling sheep (Campbell et al, 1991).…”
Section: 'Inductive Signalling' and Follicular Dominancementioning
confidence: 99%
“…Hypotheses regarding direct follicular interactions have been suggested now for many years, but have proven difficult to investigate in vivo [1]. Despite such difficulties, several extracts of follicular fluid have been proposed to play a role in folliclefollicle interactions [9][10][11][12][13][14], but their in vivo roles have yet to be established.…”
Section: Introductionmentioning
confidence: 99%